How has ESG investing impacted investment portfolios? A case study of the Malaysian civil service pension fund - Rahman, Muhammad Irfan Abdul; Lau, Wee-Yeap (Asian Journal of Economic Modelling, 2023)
Environment, social, and governance (ESG) criteria have become important in investment and risk management in recent years. ESG-mandated investment has also been trending among investors. In Malaysia, the ESG-related index known as the FTSE4Good Bursa Malaysia (F4GBM) index was first launched in December 2014. This index prompted fund managers to use the benchmark as a measure of performance. However, there has been a lack of research on ESG-related pension funds. Hence, this study examines the impact of ESG investing on the investment portfolio of the Malaysian civil service pension fund. This pension fund is managed by the Retirement Fund Incorporated (Kumpulan Wang Persaraan Perbadanan; KWAP). Using quarterly data from 2017Q3 to 2022Q3, our results show, first, that KWAP has had a higher proportion of ESG-rated securities than of non-ESG-rated securities over the last five years. Secondly, ESG-rated stocks provide higher returns than non-rated stocks in KWAP's portfolio. Thirdly, ESG-rated securities have lower risk levels than non-ESG-rated securities. This study also found that ESG-rated securities provide a higher return per unit of risk relative to non-ESG-rated stocks. As a policy implication, ESG-rated investment has impacted the pension fund by providing higher returns and lower risk. This study contributes to the awareness of the benefits of ESG investing among state-funded pension schemes.